Public Shells. - Morgan, Alfred Powell (1991)
Keywords: dept.fin; faculty_collection; sabbatical_report

Money, Inflation, and Economic Growth in Developing Countries: A Comparative Analysis - Buck, Donald T. (Southern Connecticut State College, 1973)
Keywords: Economic conditions; Economic development; Developing countries; dept.fin; faculty_collection

The Quantity Theory of Money as Applied to Economic Growth in Selected Developing Countries: Empirical Study 1956-1963 - Buck, Donald T. (1963)
Keywords: Quantity theory of money; dept.fin; faculty_collection

Non-linear characteristics of the sterling/european currency unit exchange rate: 1984–1992 - Chappell, D.; Eldridge, R.M. (International Journal of Phytoremediation, 1997)
The behaviour of the Sterling/European Currency Unit (ECU) exchange rate is examined both during the time before Britain joined the European exchange rate mechanism (ERM) and during the time of Britain's membership. During the latter period, a GARCH (1, 1) model fits the data well but during the pre-ERM period there is evidence of significant non-linear - possibly chaotic - structure in the GARCH residuals. Analysis of the dominant Lyapunov exponents and correlation dimension for the pre-ERM period suggests that the data generation process may be chaotic and this is reinforced by the highly significant BDS statistics obtained for this sample period. © 1997, Taylor & Francis Group, LLC.
1 citations (Crossref) [2023-10-31]
Keywords: Non-linearity; Sterlingecu exchange rate; dept.eco; dept.fin

The critical shift point policy for housing abandonment - Levinson, Michael S; Hsiao, J C (Atlantic Economic Journal, 1975)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/155-923-743-032-078 tex.type: [object Object]
Keywords: dept.eco; dept.fin

An Economic Interpretation of the Transportation Problem - Hsiao, J.C. (American Journal of Agricultural Economics, 1971)
1 citations (Crossref) [2023-10-31]
Keywords: dept.eco; dept.fin

The public shell: Vehicle for venture financing - Morgan, Alfred D (Journal of Business Venturing, 1988)
A public shell is generally defined as an inactive public corporation. It may or may not have assets or a publicly trading stock. However, for purposes here it must have valid SEC and domicile-State legal standing to permit its reactivation by merger with, or acquisition of, an operating company. After many years of clouded regard because of promoters' stock abuses, acceptance of using a shell to go public has considerably widened. This has been due to clarified and tighter SEC policies, rising costs of an IPO, and innovative financial uses of a shell by businessmen and investment bankers. Supply of shells probably still greatly exceeds demand for shells because of the mortality rate of the waves of new issues of recent years, the lack of cleanness of many of these shells and still lagging sophistication in their use. Nevertheless, advertising analysis indicates that in the past year alone companies "going public the back door" has at least trebled the number a decade ago. The greater part of this increase, also, appears to be accountable by ventures. For venture start-ups public access via merger with a shell can produce economies in legal/accounting costs and opportunity cost in time. It is also a means of becoming public when an initial public offering is not feasible due to market condition or nature of business. If the stock is trading it can encourage initial venture capital investment. The concept impact can vault the stock price even before earnings eventuate. Or exciting prospects can entice an exaggerated price/earnings ratio on tiny earnings. These events can even facilitate additional financing to prolong viability. But once the venture decides to use a shell for public access, the caveats of the route must be considered. In addition to valid registration and cleanness, such aspects as stockholder list, market sponsorship, control and dilution problems must be matched to the venture's financial aims. Cost of the shell can vary between $25,000-$100,000 depending on the outcome of these considerations, terms of payment, and general attractiveness of the venture entering the shell. Finally, speculative merits of shell stocks compared with the OTC Index of Industrial Stocks show that for equal holding periods, a market basket of revived-shell stocks bought soon after revival and sold around their highs, during the past decade would have produced multiple total returns compared to the less speculative index market basket. This optimum buy-sell period usually fell between 18 months and two years. But these returns presume not only sagacious timing, but that sales of stock of the typically small companies constituting shell-revivals could actually be made at the prices shown in the National Securities Dealers Pink Sheets. Beyond the optimum holding period, shell-descended companies become increasingly subject to valuation factors similar to those accorded to long established companies in related industries. © 1988.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/075-491-351-452-704 tex.type: [object Object]
Keywords: dept.fin

Rates of return on art objects, the fisher hypothesis, and inflationary expectations - Matsumoto, Keishiro; Andoh, Samuel K; Hoban, James P (The Financial Review, 1994)
After surveying the evolution of the major methodologies in inflation hedging, this study presents a unique methodology that uses principal component factor analysis to separate the effects of variability in the real rate of return from the nominal rate of return. This approach allows the effects of both anticipated and unanticipated inflation on rates of return to be estimated more precisely. This study finds that art objects perform well in terms of average real rates of return and that the market, though not perfect, integrates anticipated inflation into the rates of return. However, unanticipated inflation is very often negatively related to the rates of return. Copyright © 1994, Wiley Blackwell. All rights reserved
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/022-870-118-937-067 tex.type: [object Object]
Keywords: dept.eco; dept.fin

Controlled chain reaction as a regulatory technique - Bodo, Peter (International Advances in Economic Research, 1996)
This paper discusses a regulatory technique that consists of the use of a controlled chain reaction to influence social and economic processes. It claims that this method was employed by Hungarian control agencies to further centralize the farm sector in the 1970s. Section I of the paper presents three versions of this technique. Section II shows how the institutional structure of Hungarian agriculture made the application of this technique possible. (JEL P21).
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/075-380-606-287-914 tex.type: [object Object]
Keywords: dept.eco; dept.fin

The effect of zoning on housing construction - Thorson, James A (Journal of Housing Economics, 1997)
This paper examines whether a more restrictive zoning ordinance actually reduces construction of new housing. This may seem at first to be a trivial issue, since why else would a zoning board make the ordinance more restrictive. However, it is possible for landowners to circumvent the zoning law. For example, they can subdivide their land before the zoning change occurs. In addition, they can bargain with the local zoning officials and offer side payments, also known as exactions, for the right to develop their land. This paper examines a famous case of agricultural downzoning in McHenry County, Illinois. It finds that although the number of building permits issued did not fall immediately, in the long run the number of permits issued by the county was significantly reduced. This suggests that developers were able to anticipate the zoning change and subdivide their land before it occurred. (C) 1997 Academic Press.
31 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-739-138-771-737 tex.type: [object Object]
Keywords: dept.eco; dept.fin

An examination of the monopoly zoning hypothesis - Thorson, J.A. (Land Economics, 1996)
There have been several studies that have investigated the effect of zoning on housing prices. One hypothesis is that the restrictiveness of zoning laws will vary with the monopoly power of a town. The degree of monopoly power varies with the number of towns in the urban area. Urban areas with few zoning jurisdictions are likely to have higher housing prices than more fragmented urban areas. Previous research on this topic has shown mixed results. The results in this article suggest that towns with more monopoly power do tend to have significantly higher housing prices than more fragmented urban areas.
23 citations (Crossref) [2023-10-31]
Keywords: dept.eco; dept.fin